Penguatan Karakter Moderasi Beragama bagi Generasi Z di SMA Negeri 1 Puding Besar - Suntara, Reza Adriantika; Zahri, Tsulis Amiruddin; Tohari, Mustofa; Hijran, Muhamad; Rozani, Muhammad; Fauzi, Padlun (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The diversity of religions adhered to by Indonesian citizens is very high, characterized by the existence of six religions that are administratively and legally recognized by the state. This has become a gift from God that must be guarded and cared for properly so that differences do not trigger the growth of division. The process of maintaining harmonization of religious diversity needs to be supported in various ways, one of which is by strengthening the character of religious moderation in citizens. Religious moderation is a perspective, attitude, and behavior that takes a middle position, characterized by acting fairly and not being extreme in religion. This is a concept that needs to be instilled in Indonesian citizens, especially the younger generation as the backbone of the nation's progress in the future. Through community service carried out at SMA Negeri 1 Puding Besar, it is hoped that this can be a means of strengthening the character of religious moderation in generation Z in the Bangka Belitung Islands province, as one of the regions that also has high religious diversity. The implementation of service is carried out using socialization methods and group games, this is intended to support the goals and hopes to be achieved in service activities, namely the growth of attitudes of tolerance and cooperation.